Induced pluripotent stem cell (iPSC) line MLi005-A derived from a patient with dominant dystrophic epidermolysis bullosa (DDEB) - Sandra Ropret; Preeti Khurana; Tara Fabčič; Janina Cvetkovska; Ana Trobec; Špela Zemljič Jokhadar; Dusko Ilic; John A McGrath; Christina Guttmann-Gruber; Mirjana Liovic (Stem Cell Research, 2024)
We have generated MLi005-A, a new induced pluripotent stem cell (iPSC) line derived from skin fibroblasts of a male patient with dominant dystrophic epidermolysis bullosa (DDEB). This iPSC line may be used as a model system for studies on skin integrity, the extracellular matrix and skin barrier function. The characterization of the MLi005-A cell line consisted of molecular karyotyping, next-generation sequencing of the COL7A1 alleles, pluripotency and differentiation potentials testing by immunofluorescence of associated markers in vitro. The MLi-005A line has been also tested for ability to differentiate into fibroblasts and keratinocytes and markers associated with these cell types.